Innovative improvement of sintered ceramic electrolytes by salt infiltration - Nascimento, Rubens Maribondo do (2021)
Previously sintered (1500 °C, 4 h) dense pellets of Ce0.9Gd0.1O1.95 (GDC) were covered and heat treated with eutectic mixtures of Na2CO3 and Li2CO3 (NLC), and their electrical performance was assessed against pure GDC and chemically synthesized GDC+NLC. Microstructural analysis of NLC impregnated samples confirmed slight migration of the molten phase to the interior of the GDC pellets via grain boundaries, resulting in a significant improvement of the grain boundary conductivity, increasing with duration of heat treatment (0.5-2 h) and temperature (600 to 800 oC range). The observed total conductivity exceeded in almost 20% the corresponding values obtained for standard GDC samples. Cells tested before and after direct current polarization (0.5 V, 500 °C) showed the same electrical performance, discarding the possibility of parallel contributions of salt ions to the total conductivity. Grain boundary engineering using salt infiltration is an effective tool to improve the electrical performance of ceramic electrolytes